2022
DOI: 10.3390/ijms23137288
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Analysis of Chia Seed (Salvia hispanica L.) Bioactive Peptides Using Peptidomics and Molecular Dynamics Simulations Approaches

Abstract: Chia seed peptides (CSP) can be a source of multifunctional biopeptides to treat non-communicable diseases. However, interactions and binding affinity involved in targeting specific receptors remains unexplored. In this study, molecular simulation techniques were used as virtual screening of CSP to determine drug-like candidates using a multi-target-directed ligand approach. CSP fraction with the best bioactivities in vitro was sequenced. Then, a prediction model was built using physicochemical descriptors (hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…These sequences are able to cross the intestinal barrier without suffering any kind of modification, as explained previously. For instance, of the three peptides similar to NNVFYPF, two (RNNVFYPFE and RNNVFYPF) were identified as bioavailable in our research, whereas RNNVFYPFD demonstrated that it did not cross the barrier or was not identified in a sufficient amount.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…These sequences are able to cross the intestinal barrier without suffering any kind of modification, as explained previously. For instance, of the three peptides similar to NNVFYPF, two (RNNVFYPFE and RNNVFYPF) were identified as bioavailable in our research, whereas RNNVFYPFD demonstrated that it did not cross the barrier or was not identified in a sufficient amount.…”
Section: Resultsmentioning
confidence: 71%
“…However, there is only recently published literature reporting the identification of peptides from chia. For instance, five sequence peptides (NNVFYPF, FNIVFPG, SRPWPIDY, QLQRWFR, and GSRFDWTR) were identified by Aguilar-Toalá et al Similar to NNVFYPF, in the original hydrolysate, the peptides RNNVFYPFD, RNNVFYPFE, and RNNVFYPF were identified. Similarly, other peptides containing those identified by these authors were found in the hydrolysate under assessment and will be further discussed in the following sections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Infant formulae are also increasingly supplemented with prebiotics, probiotics, and synbiotics despite uncertainties regarding their efficacy, and a number of studies associated with the exploitation of products supplemented with probiotic/prebiotic for infants have been published in recent years. 14,15 Several clinical benefits of supplementation of infant or followon formula with single or combination probiotics , especially given beyond early infancy, had also been reported, specifically including reducing the frequency and intensity of colic and/or irritability, decreasing the risk of antibiotic use, and reducing the risk of nonspecific gastrointestinal infections by enhancing intestinal colonization of probiotics and elevating food digestibility. 16 However, a potential problem using live probiotic cells for health regulation is that they may cause some pathological changes, especially in immunodeficient patients.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The results of the Lactobacillus and Bacillus subtilis supplementation on growth performance, apparent nutrient digestibility, and stress-related indicators in dairy calves indicated that oral administration of Lactobacillus apparently improved the digestibility of crude protein . Infant formulae are also increasingly supplemented with prebiotics, probiotics, and synbiotics despite uncertainties regarding their efficacy, and a number of studies associated with the exploitation of products supplemented with probiotic/prebiotic for infants have been published in recent years. , Several clinical benefits of supplementation of infant or follow-on formula with single or combination probiotics , especially given beyond early infancy, had also been reported, specifically including reducing the frequency and intensity of colic and/or irritability, decreasing the risk of antibiotic use, and reducing the risk of nonspecific gastrointestinal infections by enhancing intestinal colonization of probiotics and elevating food digestibility …”
Section: Introductionmentioning
confidence: 99%